Seek, suffer and trust: Ese and disese in Julian of Norwich - Gillespie, V (New Chaucer Society, 2017)
Julian of Norwich's engagement with the passion meditation and ars moriendi traditions is more radically inventive than critics have noticed. Charting Julian's interactions with texts including Heinrich Suso's Horologium sapientiae, William Flete's Remedies against Tribulation, the Stimulus amoris, and the Speculum Christiani, this article proposes that Julian tactically synthesizes generic tropes to posit Christ as "the ultimate double signifier," at once physical and metaphysical, and the comfort proffered by his "destroying of death." Here, the Revelations of Divine Love is a literary artifact blending generic conventions, striving to elevate the deathbed repertoire beyond programmatic ethical schemes to a renewed understanding of Christ's redemptive suffering. Bodily sickness detaches the mind from regular consciousness, enabling fleeting, intuited access to God's ineffable compassion; Julian's abject body sees—and experiences—Christ's blood stream in the firmament. This radically deviates from the accepted generic shape of ars moriendi, refiguring Christ's sacrifice as both eternal salvation and temporal consolation. Julian redirects the genre from an affective focus on the dying process to the transcendent potential of Christus moriens as "a man dying and speaking to us." In the Revelations of Divine Love the abject liminality of "sekenes" brings the sufferer into a new affective relationship with Christ, beheld with "avisement" in the liminal space between time and immutability. Julian's newly holistic understanding of Christ's Passion affirms the potential of literature to inscribe the hypostatic sense-experience of dying revelation: her unfettered, syncretic creativity illuminates the ease offered to those who "seek, abide and trust" in God while passing beyond time.